Air Tariff Committee Report - Planning Commission (Planning Commission, 1989)
The fare structure of Indian Airlines was fixed by the Air Transport Council (ATC) three decades ago. While, it fulfilled its historical role of giving a direction and thrust to the nascent aviation sector in the country, it is no longer responsive to the vastly changed circumstances and environment. A major limitation is the telescopic profile which does not reflect fully the costs with respect to the length of haul, thereby impinging on the viability of operations and even leading to inter-modal distortions.
Planning Commission Government of India
Planning Commission Government of India